A Comparative Study of the Prescription of Memantine and Piracetam in Poststroke Aphasia - Fariborz Khorvash (مجله دانشکده پزشکی اصفهان, 2015)
Background: Aphasia is an acquired linguistic disease caused by brain injuries mostly in the left hemisphere. The symptoms can contain a vast spectrum of clinical manifestations.